Economywide and Sectoral Impacts on Workers of Brazil’s Internet Rollout - Dutz, Mark A. (World Bank, Washington, DC, 2017)
This paper is a study of the effect of Brazil's staggered Internet rollout between 2000 and 2014 on municipality employment and wages. The study uses a new, annual data set on Internet availability from the Brazil school census, with the assumption that the share of schools that have Internet access in each municipality reflects the general accessibility of Internet connections. These data are combined with Brazil's rich, matched employer-employee survey, which contains annual occupation and wage earnings information for all formally-employed workers in Brazil across all sectors, including primary, secondary, and tertiary industry groups. Contemporaneous and lagged effects are considered. The analysis finds that increased Internet access has no statistically significant net effect on aggregate employment, and has a negative effect on average wages, with a reduction in measures of wage dispersion. Brazil’s Internet rollout results in employment shifts from sectors with more limited expansion opportunities (wholesale and retail trade, public administration, and largely publicly-owned utilities, which jointly comprise almost half of the formal workforce in 2010) to sectors with more output expansion opportunities. The employment effects are positive and most pronounced in the manufacturing, transport and storage, finance and insurance, and hospitality industry groups. In the manufacturing sector, Internet access induces positive employment and wage effects in medium- and high-skill occupations.